Two new Perigrapha species from China (Lepidoptera, Noctuidae) - Saldaitis, Aidas; Ivinskis, Povilas; Borth, Robert (Zootaxa, 2012)
Two new species of Perigrapha Lederer, 1857 are described:  Perigrapha pekarskyi sp. n. and Perigrapha balazsi sp. n. from Sichuan and Shaanxi Provinces of China. Superficially the new species resemble Perigrapha hoenei Püngeler, 1914, Perigrapha extincta Kononenko, 1989 and Perigrapha gyulaipeteri Ronkay, Ronkay & Hacker, 2010 from Japan, Russia and China, respectively, but differ slightly externally as well as by genitalia and DNA barcodes.  Recent collecting records and taxonomic  studies of this group are covered in Ahn et al. 1994, Kononenko 1989, Ratnasingham & Hebert 2007 and Ronkay et al. 2010.   Acronyms for institutional repositories noted below include:  AFM: Alessandro Floriani (Milan, Italy); BBT: Balázs Benedek(Törökbálint, Hungary); FHB: Franz Hofer (Baden, Austria); GBG/ZSM: Gottfried Behounek (Grafing, Germany) / Zoologische Staatssammlung, München (Germany); HNHM: Hungarian Natural History Museum (Budapest, Hungary); NRCV: Nature Research Centre (Vilnius, Lithuania); OPB: Oleg Pekarsky (Budapest, Hungary), PGM: Peter Gyulai (Miskolc, Hungary).